2013
DOI: 10.1159/000354359
|View full text |Cite
|
Sign up to set email alerts
|

Confrontation Naming Errors in Alzheimer's Disease

Abstract: Background/Aims: Impairment in visual interpretation, semantic conception, or word retrieval may contribute to the naming errors identified in the Boston Naming Test (BNT). We investigated the possible cognitive mechanism of the naming difficulty in Alzheimer's disease (AD) by analyzing the error patterns presented in the BNT. Methods: The Chinese version of the 30-item BNT (BNT-30) was performed on 115 normal control (NC) subjects and 104 mild-to-moderate AD patients. Accurate rates after semantic and phonemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 63 publications
2
31
0
9
Order By: Relevance
“…The results have shown that individuals with dementia scored lower than those without dementia on the CLNT and BNT. This finding is consistent with the symptoms of anomia frequently found in the patients with dementia using the BNT (Bayles, Tomoeda, & Trosset, 1992;Lin et al, 2014;Salmon & Bondi, 2009), as well as with the results found in other studies using diverse naming tests (Brouillette et al, 2011;Goldman et al, 2001;Nebreda et al, 2010;Vigliecca, Aleman, & Jaime, 2007). With regard to the possible influence of age and education on the naming tests, we observed that, despite the low education of the control group, their score on the naming tests is similar to the score of the SMC group.…”
Section: Discussionsupporting
confidence: 91%
“…The results have shown that individuals with dementia scored lower than those without dementia on the CLNT and BNT. This finding is consistent with the symptoms of anomia frequently found in the patients with dementia using the BNT (Bayles, Tomoeda, & Trosset, 1992;Lin et al, 2014;Salmon & Bondi, 2009), as well as with the results found in other studies using diverse naming tests (Brouillette et al, 2011;Goldman et al, 2001;Nebreda et al, 2010;Vigliecca, Aleman, & Jaime, 2007). With regard to the possible influence of age and education on the naming tests, we observed that, despite the low education of the control group, their score on the naming tests is similar to the score of the SMC group.…”
Section: Discussionsupporting
confidence: 91%
“…To this end, previous findings about CNT were reviewed, [42][43][44][45][46] particularly those regarding the type of performance errors (see articles). [47][48][49] We make available the CACNE as a free CNT to be tested using researchers' particular samples and objectives.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Several studies suggest that the pattern is similar for healthy, MCI, and AD groups and that they only differ quantitatively in the number of errors and non-response errors, but not qualitatively. This, added to the fact that AD patients can improve their performance by using phonological clues, suggests that the semantic network might be preserved longer than thought as the information can still be accessed, and the disruption only occurs at later stages, when the non-response errors are more common (29,30).…”
Section: Characteristics Of the Deterioration Of The Semantic Networkmentioning
confidence: 99%